Penalization of Abortion in Canon and Secular Law - Jabłońska, Paulina (BIBLIOTEKA TEOLOGII STOSOWANEJ Prawda, wolność, religia, 2025)
The focus of this article is an analysis of legal regulations of abortion in Polish law and in canon law. The main goal of the article is to present the reason behind the legislator’s decision to penalise abortion. The article also shows the differences between penalisation of the crime in both law orders. In order to achieve the goal, it was necessary to analyse the regulation in both legal orders according to the applicable legal acts. The key documents are: the Act on Family Planning, Human Embryo Pro tection and Conditions of Permissibility of Abortion (1993.01.07), the Penal Code (1997.06.06) in the Polish law order and the Code of Canon Law in the Canon Law order.